Thinning or Opening: A Randomized Sibling-Embryo Pilot Trial on the Efficacy of Two Laser-Assisted Hatching Modes During the Extended Culture of Highly Fragmented Cleavage Embryos - Zhang, Ling; Zhou, Yi-er; Wu, Yue-jin; Wu, Li-mei; Li, Shi-shi; Zhang, Lin; Jin, Zhen; Shu, Chong-yi; Xu, Wei-hai; Shu, Jing (Frontiers in Endocrinology, 2022)
A randomized sibling-embryo pilot trial investigated whether two ways of laser-assisted hatching result in different blastulation and clinical outcomes after extended in vitro culture process of highly fragmented day-3 cleavage embryos. From 92 couples, a total of 315 highly fragmented day-3 embryos (the fragmentation >25%) were recruited and randomized into laser-assisted zona thinning (LAT, n=157) and opening (LAO, n=158) groups, and then underwent a blastocyst culture in vitro. The main endpoint measurements including blastocyst formation and grading as well as the clinical pregnancy after blastocyst were obtained during the treatment procedure of in vitro fertilization and embryo transfer, and then analyzed with generalized estimating equation (GEE) and/ or time-to blastocyst analysis models. A total of 166 day-3 embryos developed into blastocyst stage (52.70%), of which 97 were viable blastocysts (30.79%), and 42 top-quality ones (13.33%). LAT did not have any inferior or superior to LAO in the endpoints of either total, viable, top-quality or hatched blastocyst formation, with the ORs (95%CI) from GEE model as 1.11 (0.69-1.81), 1.40 (0.83-2.37), 0.92 (0.46-1.86) and 1.46 (0.42-1.72) respectively for LAO treatment. And the time-to blastocyst analysis showed a similar result. Additionally, no difference in clinical outcomes after blastocyst transfer was found between the two groups. The author concluded that when applying the LAHs during the extended culture of highly fragmented embryos, both LAT and LAO can generate a promising clinical outcome, and the LAT operation be equivalent to the LAO. Future well-designed, multiple-center, larger-sample investigations are required to ascertain above conclusion.